Four weeks of off‐treatment follow‐up is sufficient to determine virologic responses at off‐treatment week 12 in patients with hepatitis C virus infection receiving fixed‐dose pangenotypic direct‐acting antivirals - Liu, Chen‐Hua; Chang, Yu‐Ping; Lee, Ji‐Yuh; Chen, Chi‐Yi; Kao, Wei‐Yu; Lin, Chih‐Lin; Yang, Sheng‐Shun; Shih, Yu‐Lueng; Peng, Cheng‐Yuan; Lee, Fu‐Jen; Tsai, Ming‐Chang; Huang, Shang‐Chin; et al. (Journal of medical virology, 2024)
Early confirmation of sustained virologic response (SVR) or viral relapse after direct‐acting antivirals (DAAs) for hepatitis C virus (HCV) infection is essential based on public health perspectives, particularly for patients with high risk of nonadherence to posttreatment follow‐ups. A total of 1011 patients who achieved end‐of‐treatment virologic response, including 526 receiving fixed‐dose pangenotypic DAAs, and 485 receiving other types of DAAs, who had available off‐treatment weeks 4 and 12 serum HCV RNA data to confirm SVR at off‐treatment week 12 (SVR12) or viral relapse were included. The positive predictive value (PPV) and negative predictive value (NPV) of SVR4 to predict patients with SVR12 or viral relapse were reported. Furthermore, we analyzed the proportion of concordance between SVR12 and SVR24 in 943 patients with available SVR24 data. The PPV and NPV of SVR4 to predict SVR12 were 98.5% (95% confidence interval [CI]: 98.0–98.9) and 100% (95% CI: 66.4–100) in the entire population. The PPV of SVR4 to predict SVR12 in patients receiving fixed‐dose pangenotypic DAAs was higher than those receiving other types of DAAs (99.8% [95% CI: 98.9–100] vs. 97.1% [95% CI: 96.2–97.8], p < 0.001). The NPVs of SVR4 to predict viral relapse were 100%, regardless of the type of DAAs. Moreover, the concordance between SVR12 and SVR24 was 100%. In conclusion, an off‐treatment week 4 serum HCV RNA testing is sufficient to provide an excellent prediction power of SVR or viral relapse at off‐treatment week 12 among patients with HCV who are treated with fixed‐dose pangenotypic DAAs.